PENGARUH BIAYA PENDIDIKAN, LATAR BELAKANG SOSIAL EKONOMI, MOTIVASI DAN REPUTASI TERHADAP MINAT MAHASISWA DALAM MEMILIH PRODI S1 AKUNTANSI PERGURUAN TINGGI DI MALANG - Andriani, Evanti; Adam, Helmy (Jurnal Ilmiah Mahasiswa FEB, 2013)
The objective of research is to obtain empirical evidence about the influence ofeducation cost, socio-economical background, motivation and reputation on interest ofstudents in selecting Study Program of S1 in Accounting in higher educations in Malang.Research is implemented in 6 higher educations of Malang City, which are University ofBrawijaya (UB), State University of Malang (UM), University of Muhammadiyah Malang(UMM), State Islam University of Maulana Malik Ibrahim (UIN Maliki), Islam Universityof Malang (Unisma), and University of Merdeka (Unmer). Research method is descriptiveexplanatory study with survey approach. Therefore, data collection technique isquestionnaire. The data are then analyzed with descriptive statistic and multiple linearregression. Result of research indicates that education cost and socio-economicalbackground do not influence interest of students in selecting Study Program of S1 inAccounting in higher educations in Malang. Motivation and reputation are positive influencing interest of students in selecting Study Program of S1 in Accounting in highereducations in Malang. It is also found that education cost and socio-economicalbackground have negative correlation with interest of students in selecting Study Programof S1 in Accounting. It means that the higher the education cost or socio-economicalbackground, the lower the interest of students in selecting Study Program of S1 inAccounting.Keywords: education cost, socio-economic background, motivation, reputation, interest toselect Study Program of S1 in Accounting.